Language policy implementation in multilingual Nigeria: french and mother-tongue experience (2018)
By all standards, Nigeria is a multilingual and Multicultural state parading more than five hundred indigenous languages existing alongside English language as an official language and French language as the defacto second official language. Choosing a national language among the existing indigenous languages has become a complicated issue and a subject of controversy among the diverse ethnic groups and stakeholders in the political landscape of Nigeria due to multiplicity and plurality of languages in Nigeria. One cannot underestimate the significant value of languages in the socio- economic development of a nation. Thus, this necessitated the formulation of language policy religiously entrenched in the National Policy on Education. Though the language policy is quite laudable favouring the promotion of the indigenous languages and French language as a language of diplomacy and international relation, proper implementation of the policy provisions and most especially the teaching and learning of French language in a multicultural and multilingual country like Nigeria still suffers tremendous setback. However, this paper looked critically at the major constraints to the implementation of the language policy provisions as stated in the National Policy on Education having in focus the advantages inherent in the multilingualism and multiculturalism to promoting peaceful co-existence and socio-economic development in Nigeria. It was however recommended that government should endeavour to match policy formulation with policy implementation.